Supplementation of Glucomannan Derived from Konjac Flour Improve Glucose Homeostasis and Reduce Insulin Resistance in Diabetes Rat Models - Susanti, Nurlaili; Nissa, Choirun; Serina, Salwin N.; Ratnawati, Retty; Nurdiana; Sumitro, Sutiman B.; Soeatmadji, Djoko W.; Kalsum, Umi; Widodo, M. Aris; Widjanarko, Simon B. (Pakistan Journal of Nutrition, 2015)
Dietary fiber from glucomannan has been studied to decrease blood glucose concentration, but its mechanism in diabetes is still unclear. The aim of our research is to study the effect of glucomannan, derived from konjac flour, in rat models of diabetes including gastrointestinal function, inhibition of DPP-IV enzyme and reducing in insulin resistance. A total of 25 male wistar rats were divided into 5 groups; normal group (Normal), diabetes group (DM), diabetes group administered with 100 mg/kg BW konjac flour (DM+KF1), 200 mg/kg BW konjac flour (DM+KF2) and 400 mg/kg BW konjac flour (DM+KF3). Diabetes was induced by a combination of 60% high fructose diet and twice intraperitoneal injection of streptozotocin (25 and 30 mg/kg BW) at one week interval. Konjac flour was given according to each dose for 4 weeks. At the end of the study, blood and tissue sample were collected for subsequent analysis, while isolated intestine used to measure jejunal serous glucose concentration using everted sac technique. The results indicate that glucomannan reduced fasting blood glucose levels, improved glucose tolerance, increased jejunal serous glucose concentration at in vitro technique and decreased insulin resistance as evidenced by a decreased in HOMA-IR index and increased in PI3K levels. However, glucomannan not decreased DPP-4 levels in any dose. This results indicate that glucomannan derived from Konjac flour had antidiabetic effects through improving in glucose homeostasis and reducing in insulin resistance in rat models of diabetes.